A Case of Fibrin-Stabilizing Factor (FSF) Deficiency - Amris, C. J; Ranek, L (Thrombosis and Haemostasis, 1965)
A case with congenital deficiency of fibrin-stabilizing factor is reported. Despite severe bleeding tendency the patient had a tonsillectomy and adenotomy without complications under cover of treatment with normal plasma. No familial disposition could be demonstrated.